Boost Up Quality Assurance through Regular Evaluation of Proficiency Testing Performance - Bhatt, Rajendra Dev; Tamrakar, Dipesh; Maharjan, Bishal; Dual, Rajendra; Shrestha, Raj Kumar; Koju, Surndra; Risal, Prabodh (Annals of Clinical Chemistry and Laboratory Medicine, 2018)
Background: Participation in External Quality Assessment (EQA) program with practice of Internal Quality Control (IQC) is the excellent indicator of good laboratory practice (GLP) to assure quality services. EQA is an essential component of Quality Assurance to assess the analytical performance compared within same methods of other laboratories. It is also important to detect equipments failure, identifying reagent problems, reviewing staff training as well as to initiate and evaluate corrective action timely. Methods: This is descriptive analysis of the feedback received from EQAS body for twenty routine biochemical parameters which are most commonly performed in the Clinical Biochemistry Laboratory of Dhulikhel Hospital. Variation Index Score (VIS), Overall Mean VIS (OMVIS) and Standard Deviation Index (SDI) of all parameters for the year 2014 and 2015 were analyzed statistically. Results: On the analysis of twenty routine biochemical parameters regularly participated in EQAS, over all mean variation index score (OMVIS) of individual tests found 55%, 30% and 15% under good, very good and satisfactory category respectively. Conclusion: Participation and periodic evaluation of EQAS indicators along with practice of internal quality control has been galvanizing good laboratory practice and scientifically it boost up quality service in clinical laboratories.